Root characterization of citrus rootstocks grown in containers - Sautto Vallejo, José Maclovio; Rojas García, Adelaido Rafael; Villegas Monter, Ángel; Maldonado Peralta, María de los Ángeles; Wilson García, Claudia Yanet; Ortega Acosta, Santo Ángel (Ecosistemas y Recursos Agropecuarios, 2025)
The objective was to evaluate the root characteristics of citrus rootstocks grown in tubes with different substrates. Planting and development of the plants was carried out in Cazones, Veracruz, Mexico, and the evaluation was carried out at the Fruit Growing Laboratory, Colegio de Postgraduados, Montecillo, State of Mexico. The rootstocks were sour orange, Citrange C-35, Rangpur lime and Volkamerian lemon, transplanted in 1 L tubes filled with sand, peat-agrolite (4:1 v/v) and vega-tepojal soil (3:1 v/v). The experimental design was a randomized complete block factorial arrangement, with four repetitions of five experimental units. Six months after establishment, three repetitions of four plants per treatment were selected, and the following were evaluated: plant height, neck diameter, weight of fresh and dry root matter, number of roots per order and root length. The data were analyzed with the statistical package SAS, an ANOVA and Tukey’s comparison of means were determined (p ≤ 0.05). The variable number of roots was subjected to polynomial regression analysis. Vega-tepojal soil gave quality to aerial and radical development, being an alternative for the development of plants in the nursery, Volkamerian lemon showed greater total root length, and second, third, fourth and fifth order roots were found in all rootstocks. In the container the roots developed up to the wall, then they went to the base, where there was natural pruning. The substrate and container influenced the development and shape of the root in the four rootstocks.